Imbento-Ry: Assessing the Role of Service Crew Commitment to Inventory Counting on Inventory Management Efficiency in Quick Service Restaurant - Joel Mark Rodriguez; Lourdes Palallos (International School for Social and Business Studies, 2024)
Study design/methodology/approach: Employing a quantitative design, specifically a descriptive correlational design, while utilising a purposive sampling technique to collect the data from 171 respondents through a structured self-made questionnaire and applying the following statistical tools like mean, Pearson correlation, and regression analysis to uncover the relationship between service crew commitment and inventory management efficiency in quick service restaurant. Findings: It reveals a strong or positive correlation between service crew commitment and inventory management efficiency in quick-service restaurants. The key factors affecting service crew commitment are training programs, recognition and feedback mechanisms, standardised procedures, resource availability, and organisational culture. The regression analysis emphasises that both service crew commitment and the contributing factors significantly enhance the efficiency of inventory management. Originality/value: The uniqueness of this study is its investigation into the relationship of service crew commitment to the efficiency of inventory management in QSRs within a specific area covered by Quezon City, Philippines. This focus was not previously covered in the body of existing research. It pinpoints the factors that significantly affect crew commitment and inventory efficiency, including training, recognition, standardised procedures, availability of resources, and organisational culture. The quantitative descriptive-correlation approach presents useful data with which to act by showing a strong relationship between these variables. The authors have provided managers with practical ways to improve service crew engagement and optimise inventory processes to reduce costs and improve operational efficiency, especially in the Philippine QSR industry setting.